Effect of Sucrose as Carbon Source and Probiotic Administrations on Bacterial Population Dinamic and Water Quality in White Shrimp, Litopenaeus vannamei Culture - . Sukenda; P. Hadi; E. Harris (Jurnal Akuakultur Indonesia)
Disinfection and nutrient enrichment prior stocking of  post larvae in the pond will be affected on the growth and composition of microbe.  Attention should be taken to some factors related to deterministic and stochastic factors of aquaculture environment  in order to develop microbe community.  This study was performed to determine effect of sucrose and probiotic supplementation to shrimp culture pond on water quality profile and population dynamic on shrimp culture media.  The treatments were supplementation of sucrose as carbon source, probiotic, and sucrose + probiotic into 25 L culture medium containing white shrimp, Litopenaeus vannamei.  Shrimp were fed commercial diet containing 30% protein by 5% body weight every day.  The result of study showed that bacterial population was increased by increasing time of shrimp rearing.  Increased of bacterial population was contrary to DO value.   Bacteria grew was heterotrop and vibrio that its intensity varied during experiment.  Supplementation of sucrose supported proliferation of bacteria including heterotrop, probiotik and vibrio groups.  Specifically, interaction between probiotic bacteria and vibrio was also found.  The presence of probiotic bacteria showed a negative impact on vibrio population.  Further, development of bacteria in general was also implicated to fluctuation of ammonia concentration in pond.